(3QSGdI Edi GdTjN UOQGdOjf Gdbhfhjs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdPj NdY Ydi YHGOg Cgd GdYfGjI CSeGFg GdMSfi djMdge HPdc GdeMd GdCTQa hGUWaGge dfaSg Edi bGH bhSjf Ch COfi s
(3BNQgG (B:s
(3hEfeG fHZJ WGFaI GdLgdGA dGYde dge hJNjdhG Cf GdEfSGf dGjLhR dg Cf jdHS EdG ef TNU hGMO hde jbd HPdc CMO ef Gdbhe hGddg Gdehab JeJ GdQSGdI HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs